2006
DOI: 10.1021/bi061230e
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the ATPase Cycle of GlcV, the Nucleotide-Binding Domain of the Glucose ABC Transporter of Sulfolobus solfataricus

Abstract: ATP-binding cassette transporters drive the transport of substrates across the membrane by the hydrolysis of ATP. They typically have a conserved domain structure with two membrane-spanning domains that form the transport channel and two cytosolic nucleotide-binding domains (NBDs) that energize the transport reaction. Binding of ATP to the NBD monomer results in formation of a NBD dimer. Hydrolysis of the ATP drives the dissociation of the dimer. The thermodynamics of distinct steps in the ATPase cycle of GlcV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 44 publications
(84 reference statements)
4
21
0
1
Order By: Relevance
“…The two Walker A BmrA mutants described here are still able to bind both ATP-Mg and the 8-N 3 -ATP nucleotide analogue, albeit with a seemingly reduced efficiency, and this is in agreement with the results found after mutation of the equivalent Lys residue in other ABC transporters (30,38,(51)(52)(53). Mounting evidence supports the view that, in all native ABC transporters, the ATP-Mg binding step triggers the dimerization of the two NBDs in a transient conformation where two ATP molecules are tightly sandwiched at the NBDs interface (9,12,45,47,(54)(55)(56). While this certainly holds true for wild-type BmrA, our data suggest that this ATP-Mg dependent dimerization step is impaired in the Walker A mutants (see Figure 6), for the following reasons: (i) In contrast to wild-type BmrA, the K380R mutant hydrolyzes ATP according to Michaelis-Menten kinetics.…”
Section: Discussionsupporting
confidence: 87%
“…The two Walker A BmrA mutants described here are still able to bind both ATP-Mg and the 8-N 3 -ATP nucleotide analogue, albeit with a seemingly reduced efficiency, and this is in agreement with the results found after mutation of the equivalent Lys residue in other ABC transporters (30,38,(51)(52)(53). Mounting evidence supports the view that, in all native ABC transporters, the ATP-Mg binding step triggers the dimerization of the two NBDs in a transient conformation where two ATP molecules are tightly sandwiched at the NBDs interface (9,12,45,47,(54)(55)(56). While this certainly holds true for wild-type BmrA, our data suggest that this ATP-Mg dependent dimerization step is impaired in the Walker A mutants (see Figure 6), for the following reasons: (i) In contrast to wild-type BmrA, the K380R mutant hydrolyzes ATP according to Michaelis-Menten kinetics.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, this is expected, because Pgp has an uncoupled cycle and can hydrolyze ATP efficiently in the absence of drugs. In addition, a thermodynamic study of isolated NBD subunits of a bacterial ABC protein showed that NBD dimer formation is itself a facile and energetically favorable reaction in the absence of the transmembrane domains and transport substrate (62). In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 C, black). In contrast, we assumed a right-shifted equilibrium for step C 3 –C 4 (ΔG C4–C3 = −4.0 k T), consistent with the exergonic nature of ATP binding (Pretz et al, 2006). Finally, using standard Q-matrix techniques (Colquhoun and Sigworth, 1995), the rates for the C 1 –C 3 equilibrium were chosen to yield a K Po of 59 µM (compare Fig.…”
Section: Discussionmentioning
confidence: 99%